Error Probability Analysis of a Composite Weibull/Log-Normal Fading Channel - Mehmet BİLİM (Gazi Üniversitesi Fen Bilimleri Dergisi, 2019)
In this study, error probability of a single-input single-output (SISO) system is investigated over a composite Weibull/log-normal fading channel. We aim to study a SISO system in the composite Weibull/log-normal composite fading model which is useful in characterizing fading effects in numerous realistic communication scenarios. Therefore, a closed-form error probability expression was derived by using cumulative distribution function (CDF) of a Weibull/log-normal fading channel. The proposed error probability expression is based on CDF and is valid for different binary digital modulation types. Results that are given in this study were confirmed by computer simulations.